Design and Architecture practice research project : final report. - Vaughan, Laurene; Blythe, Richard; Boydell, Eleanor (Australia. Dept of Education and Training (DET), 2019)
The design and architecture practice research (DAP_r) project was a two-year exploration into architecture and design PhD programs with a focus on practice, undertaken in partnership between 14 Australian schools of architecture and design. DAP_r was a strategic response to Probert's 2014 observation of the lack of professionally aligned doctoral programs, and the implications this has for integration of industry and practice within the academy. Also, the project built on research by colleagues in the creative arts (Hamilton & Carson, 2015 a,b) who have likewise explored developing discipline-relevant pedagogic models for graduate research education that meet the needs of the academy and industry. The project aimed to mobilise the adoption of a practice approach to doctoral training, by enabling Australian universities to explore the applicability of a practice research model to their contexts and develop allied, networked support resources. DAP_r built on RMIT University's work to develop a design practice research PhD that situates research inside venturous practice, and borrowed its methodology from the 2013–2016 European Architecture, Design and Art Practice Training Research (ADAPT-r) project. The DAP_r project was built on a partnership model, bringing together partner institutions with extensive track records in design education linked to professions and creative practice. The core outputs and deliverables of DAP_r are outlined below, demonstrating the project's impact in sharing models of practice research, developing supervisory networks and capacity, building links with industry, and initiating and deepening discourses about creative practice research. [Executive summary, ed]